Terminal Group Effect of Conjugated Microporous Polymers for Photocatalytic Water‐Splitting Hydrogen Evolution. Issue 19 (5th September 2019) - Ding, Kang; Zhang, Qiujing; Li, Qingyin; Ren, Shijie
Abstract: Conjugated microporous polymers (CMPs) have attracted more and more attention as active materials for photocatalytic water‐splitting hydrogen evolution, however, the correlation between terminal group and hydrogen evolution performance of CMPs is rarely studied. Herein, three triazine‐based CMPs (Ta‐CMPs) with the same polymer backbone and different terminal groups (Ta‐CMP, Ta‐CMP‐N, and Ta‐CMP‐CN) are synthesized via Suzuki–Miyaura coupling reaction using different end‐capping agents. Although the Ta‐CMPs show similar porous structure and comparable band gaps, Ta‐CMP‐CN with electron‐withdrawing terminal group exhibits the highest hydrogen evolution rate (HER) of 698 µmol g −1 h −1 under visible light, while Ta‐CMP‐N with electron‐donating terminal group exhibits the lowest HER of 99 µmol g −1 h −1 . It is found that the addition of electron‐withdrawing terminal group can facilitate photoinduced charge separation, thus improving photocatalytic HER performance of the CMPs. Abstract : In order to study the terminal group effect of conjugated microporous polymers (CMPs) for photocatalytic hydrogen evolution, three triazine‐based CMPs (Ta‐CMPs) with different terminal groups are synthesized via Suzuki–Miyaura cross‐coupling reaction. Ta‐CMPs have similar morphology, porosity, and band gap, but Ta‐CMP‐CN with electron‐withdrawing group exhibits the highest H2 production rate because of its most efficient electron and hole separation ability.